2010
DOI: 10.1186/1742-9994-7-1
|View full text |Cite
|
Sign up to set email alerts
|

The influence of a hot environment on parental cooperation of a ground-nesting shorebird, the Kentish plover Charadrius alexandrinus

Abstract: BackgroundParental care often increases offspring survival, but is costly to the parents. A trade-off between the cost and benefit of care is expected, so that when care provisioning by both parents is essential for the success of young, for instance in extremely cold or hot environments, the parents should rear their young together. We investigated the latter hypothesis in a ground nesting shorebird, the Kentish plover Charadrius alexandrinus in an extremely hot environment, the Arabian Desert. Midday ground … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
133
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 164 publications
(144 citation statements)
references
References 49 publications
8
133
0
Order By: Relevance
“…The influence of ground temperature on the incubation behavior was investigated using linear mixedeffect models (Pinheiro and Bates 2000;AlRashidi et al 2010), with nest identity as the grouping structure. The model included a random intercept term for each nest.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of ground temperature on the incubation behavior was investigated using linear mixedeffect models (Pinheiro and Bates 2000;AlRashidi et al 2010), with nest identity as the grouping structure. The model included a random intercept term for each nest.…”
Section: Resultsmentioning
confidence: 99%
“…The ground temperature was included in the model as a second degree orthogonal polynomial covariate. The correlation between the time period and the temperature was also included in the model because the effect of temperature on incubation may vary throughout day (AlRashidi et al 2010). Additionally, the influence of the position of the sun on the incubation behavior was investigated using linear mixed-effect models.…”
Section: Resultsmentioning
confidence: 99%
“…Ground temperature was included in the model as second degree orthogonal polynomial covariate because Conway and Martin (2000) found that avian incubation behaviour and ambient temperature were not linearly associated. The interaction between time period and temperature was also included in the model, as the effect of temperature on incubation may vary over the day (AlRashidi et al, 2010). Total incubation percentages were arcsine squareroot transformed to achieve normality.…”
Section: Methodsmentioning
confidence: 99%
“…Each day was divided into 12 2-hour time periods. Total incubation as the percentage of time when the eggs were incubated by either parent was calculated for each period following AlRashidi et al (2010). The average temperature outside the nests was taken as the ground temperature for each period.…”
Section: Methodsmentioning
confidence: 99%
“…Twentyfive microlitres of blood were taken from either the brachial vein (adults) or metatarsal vein (chicks) and stored in Queen's lysis buffer [9]. The female and her mate were sexed in the field based on plumage characteristics and sex-specific pattern of incubation in this species [10][11][12]. Molecular sexing using P2/P8 primers to amplify W-and Z-specific chromohelicase DNA binding protein fragments [13] confirmed the phenotypic sexing results of adults and showed that all three chicks were male.…”
Section: Methodsmentioning
confidence: 99%